Ticks (Acari: Ixodidae) on wild raptors in Brazil. Issue 5 (3rd July 2020) - Teixeira, Rodrigo H. F.; Luz, Hermes R.; Pacheco, Richard C.; Onofrio, Valeria C.; Amorim, Marinete; Gazêta, Gilberto S.; da Silva, Paula De J.; Bitencourth, Karla; Marques, Sandro; Mattos Jr, Marco O.; Hernandes, Leandra S. I.; Milanelo, Liliane; et al.
ABSTRACT: This research reports ticks on wild raptors in Brazil. Between the years 1936 and 2019, 127 larvae, 230 nymphs and 34 adult ticks were collected on 92 raptors (among 27 different species) from 35 localities in distinct Brazilian biomes. Additionally, an extensive literature review on ticks on wild raptors has been carried out, demonstrating that from 1993 to 2016, 29 larvae, 81 nymphs, 29 adults and 186 indeterminate immature ticks (larvae or nymphs) were collected on 41 raptors (16 different species) in 17 distinct localities in the Brazilian territory. The following tick species were identified on wild raptors in the country: Amblyomma aureolatum (Pallas, 1772), Amblyomma auricularium (Conil, 1878), Amblyomma brasiliense Aragão, 1908, Amblyomma cajennense (Fabricius, 1787) sensu stricto, Amblyomma calcaratum Neumann, 1899, Amblyomma coelebs Neumann, 1899, Amblyomma dubitatum Neumann, 1899, Amblyomma longirostre (Koch, 1844), Amblyomma nodosum Neumann, 1899, Amblyomma ovale Koch, 1844, Amblyomma parkeri Fonseca & Aragão, 1952, Amblyomma sculptum Berlese, 1888, Haemaphysalis juxtakochi Cooley, 1946, Rhipicephalus microplus (Canestrini, 1888), and Rhipicephalus sanguineus (Latreille, 1806) sensu lato. This study is therefore a significant contribution to our knowledge of the ticks associated with Brazilian raptors.